(untitled) (The Journal of Psychology and Sociology, 2020)
Abstract: In this article, the features of emotional stability of teachers at different stages of professionalization are one of the important aspects of the formation of personality and an indicator of its improvement. The human psyche consists of rational and irrational principles interacting with each other in the context of human activity. Emotions direct and regulate the behavior and actions of humans. If we consider emotional stability on the basis of the bipolar continuum “stability-instability”, it should be recognized that the negative behavior is interconnected unstable negative behavior and experiences, including aggressive and autoaggressive reactions, incorrect perception of reality. Features of emotional stability of such teachers at various stages of professionalization negatively affect various spheres of activity, often deform personal and professional growth. With the development of the ability to emotional settlement, increasing emotional stability, a person is successful in professional activities, gets a high opportunity to make a successful career, it is easier to adapt to crisis conditions and conditions of uncertainty. Key words: teacher, emotion, stability, instability, scientific, research, methodological, experiment, professional, lecture, seminar, educational activity.